Caffeine, lactic acid, or nothing: What effect does expectation have on men’s performance and perceived exertion during an upper body muscular endurance task? - Campelo, Dara; Koch, Alexander J; Machado, Marco (International Journal of Health Sciences, 2023)
Objective: We tested the impact of subjects’ belief in an ingested substance’s ergogenic or ergolytic properties on muscular endurance performance and perceived exertion. Methods: Trained men (n = 15, age = 41 ± 4 y; body mass = 82.1 ± 15.8 kg; height = 173 ± 8 cm; experience = 7.4 ± 2.3 y) completed one set to failure at 80% repetition maximum of the bench press under three conditions. In all conditions, subjects ingested capsules of an identical, inert substance (300 mg cellulose), but, in a randomized order, subjects were told that they were either ingesting caffeine (Placebo), lactic acid (Nocebo), or cellulose (Control) and received information on the respective alleged ergogenic/ergolytic/neutral effects of each. Repetitions completed and rating of perceived exertion (RPE) were recorded. The data were analyzed among conditions using a Friedman test with post hoc analyses accomplished through Durbin-Conover tests. Spearman correlations were used to compare repetitions performed and RPE between Nocebo and Placebo conditions. Statistical significance was set at P ≤ 0.05. Results: Subjects lifted more (P < 0.001) repetitions in the Placebo condition (14.1 ± 3.0) versus Control (10.3 ± 2.9) or Nocebo (7.5 ± 2.6), while Control and Nocebo performances were similar (P = 0.192). Lower RPE was noted in Placebo versus Control (P = 0.003) and Nocebo (P < 0.001) and lower in Control versus Nocebo (P = 0.025). Subjects who performed more repetitions with Placebo tended to perform fewer repetitions under the Nocebo condition (Spearman’s Rho =–0.578). Conclusion: This study believes that the ergogenic or ergolytic properties of a substance can measurably impact upper-body muscular endurance performance and RPE in trained men.